Ethical care during COVID-19 for care home residents with dementia. (February 2021) - Cousins, Emily; de Vries, Kay; Dening, Karen Harrison
The COVID-19 pandemic has had a devastating impact on care homes in the United Kingdom, particularly for those residents living with dementia. The impetus for this article comes from a recent review conducted by the authors. That review, a qualitative media analysis of news and academic articles published during the first few months of the outbreak, identified ethical care as a key theme warranting further investigation within the context of the crisis. To explore ethical care further, a set of salient ethical values for delivering care to care home residents living with dementia during the pandemic was derived from a synthesis of relevant ethical standards, codes and philosophical approaches. The ethical values identified were caring, non-maleficence, beneficence, procedural justice, dignity in death and dying, well-being, safety, and personhood. Using these ethical values as a framework, alongside examples from contemporaneous media and academic sources, this article discusses the delivery of ethical care to care home residents with dementia within the context of COVID-19. The analysis identifies positive examples of ethical values displayed by care home staff, care sector organisations, healthcare professionals and third sector advocacy organisations. However, concerns relating to the death rates, dignity, safety, well-being and personhood – of residents and staff – are also evident. These shortcomings are attributable to negligent government strategy, which resulted in delayed guidance, lack of resources and Personal Protective Equipment, unclear data, and inconsistent testing. Consequently, this review demonstrates the ways in which care homes are underfunded, under resourced and undervalued.